Pentingnya corporate social responsibility pada strategi perusahaan dalam masa resesi ekonomi - Stefhanie, Stefhanie; Suhardjo, Iwan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Previous study researching the relationship between corporate social responsibility (CSR) and corporate financial performance (CFP) shows how important industry specificity is. Seeing by the stakeholder theory, we argue that strategic fit of CSR has a multi-dimensional characteristics, some CSR activity will be more impactful for certain industry than the others. We tested two set of hypothesis including controversial and non-controversial industry. Furthermore, we do this research by using 2019 economic recession in Indonesia throughout Covid-19 as a boundaries condition. Our studies contributes to the literature and demonstrate the role of CSR by explaining the strategic fit of CSR to specific Industry. Additional testing with mechanism in time of economic hardship adds an aspect of uniqueness to our empirical contributions.